Association of quality antenatal care and completion of eight or more antenatal care visits with skilled delivery care utilization among pregnant women in Bangladesh: A nationwide population–based study - Md. Obaidur Rahman; Md. Abdur Rauf; Yunefit Ulfa; Md. Nure Alam Siddiqi; Md. Rafiqul Islam; Kimiko Inaoka; Reiko Miyahara; Daisuke Yoneoka; Erika Ota (PLoS ONE, 2025)
Introduction Provision of quality antenatal care (QANC) services and delivery care by skilled health professionals can effectively reduce and manage complications throughout pregnancy and childbirth, leading to better maternal and neonatal health outcomes. The WHO recently updated its recommendation to at least eight antenatal care (ANC) visits. However, little is known about how QANC services and completion of eight or more ANC visits interact with skilled delivery care utilization. Methods This study utilized data from Bangladesh Demographic and Health Survey 2017–18, including 4,457 pregnant women aged 15–49 years who had given birth three years preceding the survey. Descriptive statistics were employed to analyze the study population’s characteristics and the proportion of skilled birth attendance (SBA) and facility delivery (FD) in Bangladesh. Multilevel mixed–effects logistic regression analyses were used to determine the strength of association of QANC services and completion of eight or more ANC visits with skilled delivery care utilization. Results Only one in five women received good QANC services, and one in eight completed eight or more ANC visits. The overall proportions of SBA and FD were 56.74% [95% CI: 55.27–58.20] and 53.85% [52.37–55.32] respectively. Women with eight or more ANC visits had significantly higher odds of utilizing SBA (OR: 2.11 [1.60–2.77]) and FD (OR: 2.19 [1.68–2.85]) compared to those with only 1–3 ANC visits. Likewise, good QANC services were associated with higher odds of SBA (OR: 1.72 [1.38–2.15]) and FD (OR: 1.56 [1.26–1.93]). Conclusion This study highlights the significant positive association of QANC services and adherence to the WHO–recommended eight or more ANC visits with increased skilled delivery care utilization in Bangladesh. Strengthening policies and programs to enhance the quality and frequency of ANC services can promote skilled delivery care, ensuring safe motherhood and childbirth.